Identification and multidrug resistance profiles of Escherichia coli, Salmonella, and Staphylococcus from cloacal swabs of captive yearling gharials (Gavialis gangeticus) in Chitwan National Park, Nepal - Sujan Adhikari; Himal Luitel; Swagat Khanal; Aakash Marasini (Veterinary and Animal Science, 2025)
This study focuses on the identification and antibiogram profiles of Escherichia coli, Salmonella spp., and Staphylococcus spp. isolated from cloacal swabs of captive yearling gharials (Gavialis gangeticus) at the Gharial Breeding Center, Chitwan National Park, Nepal. A total of 28 samples were collected and processed, yielding 38 isolates comprising E. coli (46.43 %), Staphylococcus spp. (46.43 %), and Salmonella spp. (42.86 %). All three bacteria were isolated in 14.29 % of samples. Antimicrobial susceptibility testing, performed using the Kirby-Bauer disk diffusion method, demonstrated high levels of resistance to commonly used antibiotics such as ampicillin and ciprofloxacin. Multidrug resistance was prevalent, with 84.62 % of E. coli and 58.33 % of Salmonella spp. isolates classified as multidrug-resistant, while all Staphylococcus spp. isolates showed resistance to three or more classes of antibiotics underscoring critical AMR challenges. The study also revealed a significant interplay between the reptilian gut microbiota and environmental factors, suggesting shared reservoirs for bacterial transmission. The findings underscore the urgent need for antimicrobial stewardship, improved environmental management, and regular health monitoring to mitigate the risks posed by antimicrobial resistance and pathogenic bacteria in critically endangered gharials. This research contributes valuable insights into the health challenges facing captive gharials and provides a basis for developing targeted conservation strategies.